2009
DOI: 10.1073/pnas.0903410106
|View full text |Cite
|
Sign up to set email alerts
|

Recent assembly of the Cerrado, a neotropical plant diversity hotspot, by in situ evolution of adaptations to fire

Abstract: The relative importance of local ecological and larger-scale historical processes in causing differences in species richness across the globe remains keenly debated. To gain insight into these questions, we investigated the assembly of plant diversity in the Cerrado in South America, the world's most species-rich tropical savanna. Time-calibrated phylogenies suggest that Cerrado lineages started to diversify less than 10 Mya, with most lineages diversifying at 4 Mya or less, coinciding with the rise to dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
809
2
76

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 879 publications
(938 citation statements)
references
References 55 publications
51
809
2
76
Order By: Relevance
“…3e-h). Savannas and tropical moist forest communities may share similar lineages across the angiosperm phylogeny, a pattern which supports previous studies that suggested that Brazilian savannas are formed by the numerous independent colonizations of lineages from nearby biomes around 4-10 Ma (Simon et al, 2009;Simon & Pennington, 2012). Conversely, the low PD values shown for SDTF communities suggest that fewer clades have succeeded in colonizing SDTF, and that consequently, SDTF is occupied by closer relatives.…”
Section: Discussionsupporting
confidence: 70%
“…3e-h). Savannas and tropical moist forest communities may share similar lineages across the angiosperm phylogeny, a pattern which supports previous studies that suggested that Brazilian savannas are formed by the numerous independent colonizations of lineages from nearby biomes around 4-10 Ma (Simon et al, 2009;Simon & Pennington, 2012). Conversely, the low PD values shown for SDTF communities suggest that fewer clades have succeeded in colonizing SDTF, and that consequently, SDTF is occupied by closer relatives.…”
Section: Discussionsupporting
confidence: 70%
“…They are common in central and southern African high rainfall savannas but, according to White [84], they are absent from West Africa. This growth form is also common in South American savannas in unrelated lineages indicating convergent responses to grass-fuelled fire regimes [85,86]. Underground trees are thought to be slow growing so that their presence indicates an ancient grassland system.…”
Section: (C) Underground Treesmentioning
confidence: 99%
“…The last decade has seen a revolution in our understanding of the evolution [17,24,25], antiquity [26 -28], distribution [29,30] and ecosystem dynamics of TGBs [14,31], as well as their role in the global carbon cycle [32]. Some of these advances have sparked controversies that are now active debates in the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%